Combination of real-value smell and metaphor expression aids yeast detection. - Kouki Fujioka; Eiji Arakawa; Jun-ichi Kita; Yoshihiro Aoyama; Toshiro Okuda; Yoshinobu Manome; Kenji Yamamoto (PLoS ONE, 2009)
BACKGROUND:Smell provides important information about the quality of food and drink. Most well-known for their expertise in wine tasting, sommeliers sniff out the aroma of wine and describe them using beautiful metaphors. In contrast, electronic noses, devices that mimic our olfactory recognition system, also detect smells using their sensors but describe them using electronic signals. These devices have been used to judge the freshness of food or detect the presence of pathogenic microorganisms. However, unlike information from gas chromatography, it is difficult to compare odour information collected by these devices because they are made for smelling specific smells and their data are relative intensities. METHODOLOGY:Here, we demonstrate the use of an absolute-value description method using known smell metaphors, and early detection of yeast using the method. CONCLUSIONS:This technique may help distinguishing microbial-contamination of food products earlier, or improvement of the food-product qualities.